Integrating Educational Theories And Islamic Perspectives For Learning Innovation - Ulvia Fatkurin Fuad; Ahmed Omar; Vikash (JMPI: Jurnal Manajemen, Pendidikan dan Pemikiran Islam, 2025)
This study investigates the integration of educational theories, pedagogical practices, and Islamic perspectives as a foundation for strengthening learning innovation in contemporary educational institutions. Employing a library research method with a descriptive–analytical approach, the study reviews both classical and modern sources across education and Islamic thought. The results reveal that educational theories, such as constructivism and critical pedagogy, provide conceptual frameworks that emphasize active engagement, collaboration, and critical reflection. Pedagogical practices operationalize these theories through strategies such as project-based learning, inquiry-based instruction, blended learning, and technology integration, thereby fostering creativity, communication, and problem-solving skills. Islamic perspectives further enrich these approaches by embedding ethical and spiritual dimensions into the learning process. Core principles such as amanah (trust), ‘adl (justice), and shura (consultation) guide educational management and classroom interactions, ensuring accountability, fairness, and inclusivity. Additionally, Sufi traditions such as tazkiyah al-nafs (purification of the soul) align with modern concepts of emotional intelligence, encouraging sincerity, empathy, and moral awareness. The synthesis of theories, practices, and Islamic perspectives thus produces models of learning innovation that are both contextually relevant and ethically grounded. This interdisciplinary integration fosters holistic learning environments that cultivate intellectual excellence, moral integrity, and spiritual growth, ensuring education serves as both a transformative and sustainable endeavor.